(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Cardiac-derived stem or progenitor cells have emerged as a possible therapeutic intervention for myocardial infarction, potentially ameliorating the devastating effects caused by inadequate blood flow to the heart. The first human clinical trials using these myocardial-derived cells have recently started, but scientific controversy exists regarding the efficacy and origin of some of these stem cells in preclinical animal models. Systematic review of the current literature on CSCs in ischaemic cardiomyopathy can provide useful additional information on the use of CSCs in pre- clinical trials. By combining all available data, we can adequately compare the different types of cells being used and possibly identify factors that influence cardiac stem cell therapy in general. This protocol provides a thorough description of the methodology that will be used in our systematic review and meta-analysis of all preclinical animal studies involving cardiac stem cell treatment for ischaemic cardiomyopathy.